Ipilimumab and Pembrolizumab Mixed Response in a 41-Year-Old Patient with SMARCA4-Deficient Thoracic Sarcoma: An Interdisciplinary Case Study - Anžič, Nina (Case Rep Oncol, 2021)
SMARCA4-deficient thoracic sarcoma is a newly described entity of thoracic sarcomas with a poor prognosis, defined by poorly differentiated epithelioid to rhabdoid histomorphology and SMARCA4 gene inactivation. We present a case of a SMARCA4-deficient thoracic sarcoma in a 41-year-old male with a smoking history who presented with an upper anterior mediastinal mass, after seeking medical evaluation for increasing thoracic pain, odynophagia, and dizziness. The biopsy confirmed a large cell tumor with an epithelioid to rhabdoid histomorphology, positive for EMA, CD99, vimentin, TLE1, INI1, PAS-positive cytoplasmic granules, and PD-L1 (100% of tumor cells). High TMB and HRD scores were displayed in the tumor. The histology and immunophenotype of the mass were in line with the diagnosis of SMARCA4-deficient thoracic sarcoma. In the course of his treatment, the patient showcased a partial response to pembrolizumab and the combination of pembrolizumab and ipilimumab. This case report highlights the importance of recognizing SMARCA4-deficient thoracic sarcoma as an individual entity and supports the importance of checkpoint inhibition therapy for SMARCA4-deficient thoracic sarcomas, particularly in cases with a high TMB and PD-L1 expression.